KERJA SAMA THE GLOBAL FOODBANKING NETWORK (GFN) DAN FOODCYCLE INDONESIA DALAM MEMINIMALISIR SAMPAH MAKANAN DI INDONESIA - Salsabilla, Aulia; Pakpahan, Saiman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
The Global FoodBanking Network (GFN) is an international NGO and FoodCycle Indonesia is a national NGO that collaborates in efforts to minimize food waste in Indonesia starting from 2019 until now. In collaborating as two NGOs, The Global FoodBanking Network (GFN) and FoodCycle Indonesia have an important role in minimizing food waste in Indonesia as implementers, catalysts and partners according to the NGO theory of David Lewis dan Nazeen Kanji. The Global FoodBanking Network (GFN) and FoodCycle Indonesia contribute by distributing leftover food that is still good and fit for consumption to people in need, inviting anyone, both individuals and groups, to donate, introducing the program they created as a form of education and reminder to people. to minimize food waste, as well as providing practical skills training through the FoodCycle Farm program. Keywords: International cooperation, NGO, The Global FoodBanking Network (GFN), FoodCycle Indonesia